(untitled) (World Bulletin of Social Sciences, 2023)
This article focuses on the issue of how critical thinking is important in teaching and the ways to develop significantly this skill with students in all stages of education. Furthermore there is some information about the features of critical thinking and the activities are given as samples for using in the classroom when the teachers develop their students` critical thinking abilities.